The journey of decellularized vessel: from laboratory to operating room - Kang, Chenbin; Yang, Hongji (Frontiers in Bioengineering and Biotechnology, 2024)
Over the past few decades, there has been a remarkable advancement in the field of transplantation. But the shortage of donors is still an urgent problem that requires immediate attention. As with xenotransplantation, bioengineered organs are promising solutions to the current shortage situation. And decellularization is a unique technology in organbioengineering. However, at present, there is no unified decellularization method for different tissues, and there is no gold-standard for evaluating decellularization efficiency. Meanwhile, recellularization, re-endothelialization and modification are needed to form transplantable organs. With this mind, we can start with decellularization and re-endothelialization or modification of small blood vessels, which would serve to address the shortage of smalldiameter vessels while simultaneously gathering the requisite data and inspiration for further recellularization of the whole organ-scale vascular network. In this review, we collect the related experiments of decellularization and post-decellularization approaches of small vessels in recent years. Subsequently, we summarize the experience in relation to the decellularization and post-decellularization combinations, and put forward obstacle we face and possible solutions.